2021
DOI: 10.1111/cns.13715
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane preconditioning protects experimental ischemic stroke by enhancing anti‐inflammatory microglia/macrophages phenotype polarization through GSK‐3β/Nrf2 pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Hypoxic preconditioning-induced Nrf2 activation occurs in a GSK-3β phosphorylation-dependent manner and enhances anti-inflammatory microglia phenotype polarization after cerebral I/R, thus favoring ischemic tolerance and protective processes (Cai et al, 2021 ). Furthermore, ischemic/hypoxic conditioning therapeutics can influence microglia dynamics, including migration, phagocytosis, and proliferation at early stages after brain ischemia and reperfusion, promoting brain repair (Dang et al, 2018 ).…”
Section: Microglia a Promising Target For Neuroprotection In Ischemic...mentioning
confidence: 99%
“…Hypoxic preconditioning-induced Nrf2 activation occurs in a GSK-3β phosphorylation-dependent manner and enhances anti-inflammatory microglia phenotype polarization after cerebral I/R, thus favoring ischemic tolerance and protective processes (Cai et al, 2021 ). Furthermore, ischemic/hypoxic conditioning therapeutics can influence microglia dynamics, including migration, phagocytosis, and proliferation at early stages after brain ischemia and reperfusion, promoting brain repair (Dang et al, 2018 ).…”
Section: Microglia a Promising Target For Neuroprotection In Ischemic...mentioning
confidence: 99%
“…48,49 Therapeutic effects include a reduction in lesion volume, improvement of functional outcome, 50 attenuation of reactive astrogliosis, 51 and promotion of anti-inflammatory microglial and macrophage phenotypes. 52 Research revealed numerous molecular pathways that mediate the beneficial effects of volatile anesthetics.…”
Section: Inhalative Substancesmentioning
confidence: 99%
“…Receptors, signaling pathways and transcription factors also influence macrophage polarization. Sevoflurane pretreatment promotes the formation of an anti-inflammatory phenotype in microglia/macrophages by up-regulating the phosphorylation of GSK-3β and Nrf2 nuclear transposition, and it has a neuroprotective effect on middle cerebral artery occlusion (MCAO) ( Cai et al, 2021a ). However, sevoflurane inhibits FoxO1, regulates p21 and increases the expression of TNF-α, monocyte chemotactic protein-1 (MCP-1) and IL-6, which may increase the polarization of M1 macrophages, induce a central nervous system (CNS) inflammatory response, and lead to cognitive impairment ( Fu et al, 2020 ).…”
Section: Macrophages and Anestheticmentioning
confidence: 99%
“…Dexmedetomidine and propofol inhibit the expression of lipopolysaccharide (LPS)-stimulated high mobility group box 1 (HMGB1) in macrophages ( Chang et al, 2013 ; Jia et al, 2017 ). The volatile anesthetic sevoflurane modulates macrophage recruitment, polarization, differentiation, apoptosis and pyroptosis by regulating the caspase-1, reactive oxygen species (ROS), forkhead box O1 (FoxO1), p21, and glycogen synthase kinase-3 (GSK-3β)/nuclear factor-E2-related factor 2 (Nrf2) pathways, which are involved in local immunity and tumor growth ( Jin et al, 2013 ; Fu et al, 2020 ; Sztwiertnia et al, 2020 ; Cai et al, 2021a ). Opioids, such as morphine, also inhibit the phagocytosis of macrophages and are associated with the reduction of macrophage colony-stimulating factor-induced proliferation and differentiation ( Sacerdote et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%